Lactobacillus plantarum HFY05 Attenuates Carrageenan-Induced Thrombosis in Mice by Regulating NF-κB Pathway-Associated Inflammatory Responses - Zeng, Shi; Yi, Ruokun; Tan, Fang; Sun, Peng; Cheng, Qiang; Zhao, Xin (Frontiers in Nutrition, 2022)
In this study, a carrageenan-induced thrombus model was established in mice to observe the ability of Lactobacillus plantarum KFY05 (LP-KFY05) to inhibit thrombosis through an NF-κB-associated pathway. Biochemical analysis, microscopical observations, quantitative polymerase chain reactions (qPCR) and western blot analysis were used to examine the relevant serum and tissue indexes, and the composition of intestinal microorganisms was determined by examining the expression of microorganisms in feces. The results showed that LP-KFY05 could markedly reduce the degree of black tail in thrombotic mice; increase the activated partial thromboplastin time (APTT); and reduce the thrombin time (TT), fibrinogen (FIB) level, and prothrombin time (PT). LP-KFY05 could also reduce tumor necrosis factor alpha (TNF-α), interleukin-6 (IL-6), and interleukin-1 beta (IL-1β) levels in the sera and kidneys of thrombotic mice. Hematoxylin and eosin staining showed that LP-KFY05 could reduce renal tissue lesions and tail vein thrombosis. qPCR results showed that LP-KFY05 could down-regulate nuclear factor kappa-B (NF-κB) p65, IL-6, TNF-α, and interferon γ (IFN-γ) mRNA expression in renal tissues and NF-κB p65, intercellular cell adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), and E-selectin mRNA expression in tail vein vascular tissues of thrombotic mice. Western blot analysis showed that LP-KFY05 also down-regulated NF-κB protein expression in renal and tail vein vascular tissues of thrombotic mice. Lastly, LP-KFY05 increased the abundances of Bacteroidetes, Lactobacillus, and Bifidobacterium and decreased the abundance of Firmicutes. These results show that LP-KFY05 can reduce inflammation and inhibit thrombosis in thrombotic mice, and the effects of the high concentration of LP-KFY05 was best, which were similar to the effects of dipyridamole.